Extra-lymphatic filariasis at reconstructive surgery flap site recurrence of head and neck cancer. (2016) - Shetty, Nishitha; Joshi, Amit; Noronha, Vanita; Dhumal, Sachin; Epari, Sridhar; Prabhash, Kumar; Patil, Vijay
Abstract: Filarial infection is commonly encountered in the Indian subcontinent. Here we present a clinical image of filarial infestation at the site of recurrence of head and neck cancer.